Effect of Recovery Supplementary Feeding on Height Improvement in Stunted Toddlers: A Study at Mijen Health Center, Semarang, Central Java - Ariyani Lutfitasari; Alya Aulia Rahmayani; Erna Kusumawati; Dewi Puspitaningrum (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The level of child malnutrition in Indonesia is considered to be high in the world. Some efforts were granted including the provision of supplementary food in some areas of Indonesia. The effort is chosen as a step to fulfill the need for nutrition in children. Objectives: This study aims to determine the relationship between providing supplementary food recovery and height gain in stunted toddlers at Mijen Health Center, Semarang City, Central Java. Method: This research employed a descriptive quantitative approach with a cross-sectional survey design. A checklist was used in the study. The sample consisted of 50 stunted toddlers selected through saturation sampling. Statistical analysis utilized the Chi-Square test with a confidence level of 95%. Results: As many as 52% of respondents have spent the recovery supplemental feeding (PMT) consumed for 60 days. The height of toddlers given recovery PMT increased, which previously had an average Z-score of -2.03, then increased to -1.86. Based on the results of the Chi-Square test, a P-Value of 0.009 (<0.05) can be interpreted that there is a significant relationship because the P-Value is <0.05; OR of 5,500 can be interpreted that recovery supplements that are not eaten out have a 5,500 times greater risk of no increase in height of stunted toddlers compared to toddlers who consume recovery PMT. Conclusion: This study concludes that there is a relationship between the provision of recovery supplementary food and height gain in stunted toddlers in the operational area of Mijen Health Center, Semarang City, Central Java.